Strategic Communication Through Instagram: How STMIK IDS Builds Its AI Campus Identity - Kumara, Dennis; Tiawan, Tiawan; Oktaviani, Rani Chandra (Communicare : Journal of Communication Studies, 2025)
STMIK Indo Daya Suvana, also known as IDS Digital College, is undergoing a digital transformation aimed at establishing its reputation as an “AI Campus.” This paper examines an institution that has begun using Instagram as a communication strategy during its transformation. In the context of higher education, where competition is intensified by digital presence, social media has become essential for influencing student recruitment. This study employs a qualitative research design that combines document analysis with in-depth interviews. The research examines Instagram content, analyzing themes including posts, captions, images, and audience engagement. To enhance the analysis, interviews were held with key participants from STMIK IDS. Analyzing Instagram as a social media platform, this study found that it is used not only to advertise events and programs but also to tell stories about campus identity, values, and future direction. Content related to artificial intelligence (AI), digital innovation, and campus activities is presented in a persuasive and engaging style, helping to build STMIK IDS’s image as an institution focused on AI. In conclusion, effective communication on Instagram is not merely visual. It requires internal strategies that enhance understanding of prospective students while ensuring alignment with audience expectations. This case study shows that a digital platform can function as a branding channel while connecting the institutional image and public perception.